Evaluation of Healthcare Economics of OECD Countries: Multi-Objective Statistical Optimization Model - Abdulkadir Atalan; Cem Çağrı Dönmez (Acta Infologica)
Healthcare systems comprise the most crucial factors affecting countries economically. In this study, the infrastructure and economic structure of healthcare systems belonging to the Organization for Economic Co-operation and Development (OECD) countries are discussed to evaluate the healthcare expenditures (HE) and healthcare expenditures per capita (pcHE) of OECD members. We have identified factors related to healthcare economics and analyzed the significance ratios of these factors to calculate the feasible values of the factors affecting the healthcare systems in the OECD members by statistical optimization analysis. Within the feasible values obtained by using a multi-objective optimization model (MOOM) because of statistical analysis, the HE of OECD countries was minimized, and an improvement of 29.13% was achieved. The second objective function aimed to maximize the pcHE that was estimated to be at least $5,282.37 for the OECD members. Consequently, in countries that do not have a social healthcare system, it is perceived that HE amounts are excessive. The fundamental reason for this situation represents the healthcare sector’s perception as a business in those countries.